In Vitro Evaluation of Turmeric Extract (Curcuma domestica) Antibacterial Activity against Staphylococcus aureus Causing Dental Abscess - Ni Putu Widani Astuti; I Wayan Agus Wirya Pratama; Ilma Yudistian (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Dental abscess is a common odontogenic infection characterized by pus accumulation due to an inflammatory response to microorganism invasion. Staphylococcus aureus is a major opportunistic pathogen frequently found in periapical abscesses and endodontic infections. Increasing bacterial resistance to conventional antibiotics has become a global health concern. Turmeric (Curcuma domestica) possesses antibacterial activity attributed to curcumin and phenolic compounds. Materials and Methods: This experimental laboratory study with a post-test only control group design was conducted at the Microbiology Laboratory, Faculty of Dentistry, Airlangga University in October 2023. Turmeric extract at 50%, 75%, and 100% concentrations was tested against Staphylococcus aureus isolates using the disc diffusion method on Mueller-Hinton Agar. Data were analyzed using One-Way ANOVA and LSD post-hoc test (α = 0.05). Results and Discussion: Phytochemical screening detected six active compounds: saponins, phenols, steroids, alkaloids, flavonoids, and tannins. Turmeric extract at 100% produced the highest inhibition zone of 16.38 mm, compared to 23.20 mm for the positive control (0.2% chlorhexidine). ANOVA analysis showed significant differences among groups (F = 277.78; p < 0.05), with a positive correlation between increasing extract concentration and antibacterial effectiveness. Conclusion: Turmeric rhizome extract at 50%, 75%, and 100% concentrations demonstrates significant antibacterial activity against Staphylococcus aureus, with effectiveness increasing proportionally to concentration, showing potential as a natural antibacterial alternative therapy in dentistry, especially in instances of dental abscesses.